2013
DOI: 10.1002/jaba.49
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Programmed Treatment-Integrity Errors During Discrete-Trial Instruction

Abstract: This study evaluated the effects of programmed treatment-integrity errors on skill acquisition for children with an autism spectrum disorder (ASD) during discrete-trial instruction (DTI). In Study 1, we identified common treatment-integrity errors that occur during academic instruction in schools. In Study 2, we simultaneously manipulated 3 integrity errors during DTI. In Study 3, we evaluated the effects of each of the 3 integrity errors separately on skill acquisition during DTI. Results showed that particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

10
148
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 100 publications
(159 citation statements)
references
References 14 publications
10
148
1
Order By: Relevance
“…We used dual mastery criteria targeting global and reinforcer-component integrity because performance on the reinforcer component was consistently low across all four therapists during baseline. Furthermore, Carroll et al (2013) demonstrated that errors in consequence delivery impeded the skill acquisition of children. Therefore, we believed improvements in reinforcer integrity to be clinically indicated.…”
Section: Response Measurementmentioning
confidence: 99%
See 4 more Smart Citations
“…We used dual mastery criteria targeting global and reinforcer-component integrity because performance on the reinforcer component was consistently low across all four therapists during baseline. Furthermore, Carroll et al (2013) demonstrated that errors in consequence delivery impeded the skill acquisition of children. Therefore, we believed improvements in reinforcer integrity to be clinically indicated.…”
Section: Response Measurementmentioning
confidence: 99%
“…Researchers have systematically manipulated levels of integrity and demonstrated functional relationships between integrity and treatment outcomes (e.g., Carroll et al 2013;DiGennaro Reed et al 2011;St. Peter Pipkin et al 2010;Wilder et al 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations